Overexpressed L20 Rescues 50S Ribosomal Subunit Assembly Defects of bipA-Deletion in Escherichia coli - Choi, Eunsil; Jeon, Hyerin; Oh, Jeong-Il; Hwang, Jihwan (Frontiers in Microbiology, 2020)
The BipA (BPI-inducible protein A) protein is highly conserved in a large variety of bacteria and belongs to the translational GTPases, based on sequential and structural similarities. Despite its conservation in bacteria, bipA is not essential for cell growth under normal growth conditions. However, at 20°C, deletion of bipA causes not only severe growth defects but also several phenotypic changes such as capsule production, motility, and ribosome assembly, indicating that it has global regulatory properties. Our recent studies revealed that BipA is a novel ribosome-associating GTPase, whose expression is cold-shock-inducible and involved in the incorporation of the ribosomal protein (r-protein) L6. However, the precise mechanism of BipA in 50S ribosomal subunit assembly is not completely understood. In this study, to demonstrate the role of BipA in the 50S ribosomal subunit and possibly to find an interplaying partner(s), a genomic library was constructed and suppressor screening was conducted. Through screening, we found a suppressor gene, rplT, encoding r-protein L20, which is assembled at the early stage of ribosome assembly and negatively regulates its own expression at the translational level. We demonstrated that the exogenous expression of rplT restored the growth of bipA-deleted strain at low temperature by recovering the defects in ribosomal RNA processing and ribosome assembly. Our findings suggest that the function of BipA is pivotal for 50S ribosomal subunit biogenesis at a low temperature and imply that BipA and L20 may exert coordinated actions for proper ribosome assembly under cold-shock conditions.